(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
According to the latest data from the World Health Organization, 20-30% of patients who apply to the surgical department have 2 or more additional diseases, and this figure is increasing from year to year. This, in turn, requires surgical treatment, as in any disease. According to various sources, the prevalence of proctological diseases is very high, from 120 to 186 per 1000 population, of which from 10 to 50% of the population is in need of treatment, and in 75% of cases it is necessary to perform surgery.